The Productivity and Income of Corn Farming Business through the Application of Biological Fertilizers - Joni Karman; Suparwoto Suparwoto; Yanter Hutapea (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
The use of microbes’ research as biological fertilizers in order to increase corn production had been performed, but the analysis of farming business related to this matter has not been conducted. This research aimed to determine the effect of one of the biological fertilizers, which was Agrimeth, on the seeds of various composite corns to the growth factors, the productivity of corn farming in dry land, and the amount of income that was obtained. This research was conducted in Betung Village, Betung Sub-District, Banyuasin Regency, South Sumatra. The corn varieties used were Bima 10, Bima 19, and Sukmaraga. The results showed that the seed treatment of corn seeds with Agrimeth showed an improvement trend of plant height, number of leaves, cob length and diameter, weight of 100 dry shelled grains, dry shelled production, and R / C in each variety. The application of Agrimeth biological fertilizers increased corn farming in dry land with R / C 2.79; 2.65; and 1.82 for each Bima 10, Sukmaraga and Bima 19 varieties.